Consumer’s perceived communicational risks in predicting internet-based shopping intention - Bashir, Shahid; Aslam, Manan; Faridah Ibrahim,; Kamaljeet Kaur, (Penerbit Universiti Kebangsaan Malaysia, 2017)
It is widely known in the related literature that consumer’s perceived communicational risks act as a chief barrier to their online purchase decision. Though, in such regards, few of the most recent text focused precisely towards a modified fact that the consumer’s shopping intention may depend on their perceived communicational risks in an online trade. Still, a very little attention has been kept to this precise concept leaving an academic gap. This research aims to contribute towards closing the research issue as such. By gathering data through existing literature, the researchers probe into the total force. The findings uncovered that the global web vendors’ efforts to lessen certain types of communicational risks such as performance, financial, psychological and time will improve consumers’ intentions to purchase online. Consequently, the future researches are recommended to be undertaken in order to explore and refine the measurement scales used to measure perceived communicational risk and online purchase intention. Moreover, a longitudinal study is also recommended to discover how the consumers’ behavioral intention toward Internet changes over time due to the rapid development of this communicational technology.